Graves’ disease in children with Down syndrome - Cebeci, Ayse Nurcan; Schempp, Vera; Förtsch, Katharina; Gohlke, Bettina; Marx, Martin; Dörr, Helmuth-Günther; Wölfle, Joachim (Endocrine Connections, 2024)
While subclinical or overt hypothyroidism are common in Down syndrome (DS); Graves’ disease (GD) is rare (ranges 0.6–3%). We aimed to evaluate the clinical features, course, and treatment of GD in children with DS and compare them with those without DS. Among 161 children with GD, 13 (8 female, 5 male) had DS (8%). Data were collected retrospectively from patients’ medical records. The mean age at diagnosis was 10.6 ± 4.5 years, with a female-to-male ratio 1.6:1. The main symptoms were weight loss (n = 6), increased irritability (n = 3), and increased sweating (n = 3). None had orbitopathy. Seven of 11 patients with a thyroid ultrasound at diagnosis had a goitre. On admission, all had thyroid-stimulating hormone (TSH) <0.01 mU/L (normal range (NR): 0.51–4.30), free triiodothyronine, free thyroxine (mean ± s.d.), and thyrotrophin receptor antibodies (median, range) were 22.2 ± 10.2 pmol/L (NR: 3.5–8.1), 50.2 ± 18.7 pmol/L (NR 12.6–20.9), and 17.0 (2.89–159.0) U/L (NR <1), respectively. Patients were treated either with methimazole (n = 10) or carbimazole (n = 3), a dose of 0.54 ± 0.36 mg/kg/day. The treatment was ‘block and replace’ in ten patients and ‘dose titration’ in three patients, with a mean duration of 43.4 ± 11.0 months. Of 13 patients, four are still receiving primary treatment, three are in remission, one patient had two medically treated recurrences, three underwent surgery without complications, and two patients were lost to follow-up. Our data show that the clinical course of GD in patients with DS was similar to those without DS and suggest that a prolonged medical therapy should be the preferred option.
CRIS-Team Scopus Importer:2024-06-28
Keywords: anti-thyroid drug medication; autoimmune thyroiditis; Down syndrome; Graves’ disease; hyperthyroidism

SIADH as a Rare Complication of Foramen Magnum Stenosis in an Infant With Achondroplasia. - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Rompel, Oliver; Wölfle, Joachim (JCEM Case Reports, 2024)
Achondroplasia is the most common skeletal dysplasia and is associated with serious complications such as foramen magnum stenosis (FMS). This case report describes an infant with achondroplasia who presented with a syndrome of inappropriate antidiuretic hormone secretion (SIADH), secondary to significant FMS and myelocompression. A 2-month-old boy with prenatally diagnosed achondroplasia was referred due to disordered breathing and altered consciousness. On admission, apathy, hypotonus, and hypothermia with typical features of achondroplasia were noticed. Laboratory investigations revealed severe hyponatremia and hypochloridaemia with normal glucose and urea levels. The diagnosis of SIADH was made based on low serum osmolality in the presence of high urine osmolality, along with an elevated copeptin level. An emergency computerized tomography showed a high-grade stenosis at the cranio-cervical junction; subsequent magnetic resonance imaging demonstrated myelocompression. The patient underwent decompression surgery the next day; serum osmolality increased after the operation. Spontaneous breathing after extubation was sufficient whereas tetraplegia persisted despite intensive physiotherapy. Clinicians should be aware of SIADH as a presenting sign of FMS in children with achondroplasia. Further discussion is warranted regarding improving parental education and timing of screening recommendations.
EVALuna2:582017

SIADH as presenting feature of foramen magnum stenosis in a 2-month-old infant with achondroplasia (ACH): case report and discussion on management of infants with ACH in order to reduce the risk of serious complications - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Wölfle, Joachim (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07